Seasonal swim programs & how they relate to competitive performance - Stewart, A. (coachesinfo.com)
The findings of the research of the training programs for a summer and winter season twenty-four of the best swim coaches in New Zealand provided for their best age-group sprint- and middle-distance swimmers.